Shariah Compliant Investment : EPF’s Shariah Saving Scheme / Fatin Azuahana Mohamad - Mohamad, Fatin Azuahana (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Millions of employees take part in private retirement plans. Shariah Saving scheme is an initiative by EPF to enable EPF members to choose their accounts to be managed and invested in accordance with Islamic Shariah principles. This plan has a great social and economic impact to the nation. As Muslim investors in Malaysia, the most prefer EPF’s Shariah Compliant Scheme. Most of the results explained the respondent support Shariah Saving scheme. But there are also respondents who still are not aware about it. This study will be significant for the contributors who want to change or convert their Conventional Saving scheme to Shariah Saving scheme and will definitely help Malaysian citizen who contribute to EPF saving scheme and also for the citizen who will contribute in the future for example, the student who will work in private and Non-Pensionable Public Sector. This study is believed to help the institution and also the government to promote to the citizen to convert their scheme to Shariah Saving scheme as we a Muslim need to invest in Shariah compliance scheme as the benefits or profit that we get is pure from interest (riba), uncertainty (gharar) and gambling (maysir). Muslim respondents are preferred Shariah Saving scheme because it follows Shariah guidelines, invest to permissible activities, rate of dividend is not fixed like the Conventional Saving scheme. It is better to improve to the people who have been contribute in the Shariah Saving scheme or Conventional Saving scheme and people who will contribute to one of the saving scheme in future.